A PRÁTICA ESCOLAR SOB ESCRUTÍNIO - Geraldi, João Wanderley (Organon, 2012)
The aim of this article is to present some tendencies in research of brazilianuniversities, taking into account the areas of Applied Linguistics, Psycology of Education andLibrarianship. As object of our investigation, we selected fifty-three studies (master anddoctoral thesis) produced from 1980 untill 1995, about the same theme: questions of learningand teaching in formal and informal situations.The results of this study show three majoremphasis: a) relations established between subjects and writing; b) reflections on thecharacteristics of language based on references of school process; c) production of differenttheorectical assumptions and practical activities to be developed in the classroom.